Cytokine Detection and Modulation in Acute Graft vs. Host Disease in Mice - A. C. Knulst; G. J. M. Tibbe; C. Bril-Bazuin; E. G. Breedland; A. van Oudenaren; R. Benner; H. F. J. Savelkoul (Hindawi Limited, 1994)
A murine model for acute lethal graft vs. host disease (GVHD) was used to study the role that a number of cytokines play in the development of lethal GVHD. In this study we focused on the role of IL-1, IL-2, IL-4, IL-6, IFN-γ and TNF-α. Lethally irradiated (C57BL × CBA)F1 mice were reconstituted either with 107 allogeneic BALB/c spleen cells or with a similar number of syngeneic cells, as a control. A significant rise in serum levels of IL-6, TNF-α and IFN-γ levels was found in allogeneically reconstituted mice. This is in contrast to the syngeneic control group in which no rise was seen. Serum IL-2 and IL-4 levels were below the detection limit. In the supernatant of Con A stimulated spleen cells from allogeneically reconstituted mice IL-6, IFN-γ and TNF-α concentrations were increased. The expression of mRNA for cytokines as detected by reverse transcription PCR was studied in spleen cells. In the allogeneic reconstituted mice the mRNA expression of IL-1α, IL-2, IL-6, IFN-γ and TNF-α displayed faster kinetics compared with that in syngeneic reconstituted mice. The effect of treatment with recombinant cytokines, antibodies to cytokines and to cytokine receptors on the development of GVHD was investigated. Administration of recombinant IL-2 to allogeneically reconstituted mice strongly increased the morbidity and mortality whereas injection of IL-1α and TNF-α did not influence survival. Administration of antibodies against IL-2 or the IL-2 receptor decreased the morbidity and mortality. Anti-IL-6, anti-IFN-γ, and anti-TNF-α mAB, on the other hand, did not affect the morbidity and mortality of GVHD. The results of this study suggest successive waves of cytokine-secreting cell populations consistent with the induction of an inflammatory response in the development of acute GVH disease.